Health status of traffic police personnel in Chennai city - S., Sridher; S., Thulasiram; Rishwanth, R; G., Sakthivel; V., Rahul; Maheswari R., Uma (Public Health Review: International Journal of Public Health Research, 2017)
Background: The work environment constitutes an important part of man’s total environment, so health to a large extent is affected by work conditions. These personnel have to undergo physical strain in an environment polluted by fumes, exhaust of vehicles, use of blowing horns, blow of dust in the air by the speeding vehicle, under hot sun, etc. Objective: To assess the health status of the traffic police personnel in Chennai city. Methodology: Cross sectional study was conducted among 139 traffic police personnel in Chennai city. Afterobtaining informed consent,information regarding socio-demographic profile, job experience and physical health profile was collected using a pre-structured proforma. Results: Among the study population, 134 (96.4%) were males and 5 (3.6%) were females. Thirty two (23%) were diabetic, 32 (23%) were hypertensive, 17 (12.2%) had respiratory problems, 26 (18.7%) had skin problems, 70(50.4%) complained of low back pain, 34 (24.5%) reported eye problems, 20 (14.4%) had low PEFR, and 18 (12.9%) were found to have varicose veins by Trendelenberg’s test. Significant association (p<0.05) was found between years of service with diabetes, hypertension, abnormal waist circumference and usage of personal protective equipment (maskand sunglasses). Conclusion: Regularscreening and health education programs need to be implemented. Lifestyle modification, smoking and alcohol control and stress alleviation should be an integral component of these health-related activities.